The Roles of Invertebrates in the Urban Soil Microbiome - Bray, Natalie; Wickings, Kyle (Frontiers in Ecology and Evolution, 2019)
Urban soils differ from those in other managed ecosystems in many ways, including their heterogeneity, unique organic matter inputs and exposure to past and present anthropogenic activities. Soil processes in urban systems are influenced by the microbiome, specifically bacterial and fungal communities that are currently recognized as the primary drivers of soil organic matter dynamics. However, our understanding of biotic controls on microbial communities is incomplete, particularly in regard to the roles of invertebrates. We aim to highlight how invertebrates and their interactions with microbial communities may shape ecosystem processes in urban systems. We discuss three primary pathways through which invertebrates are known to influence the soil microbiome: dispersal of microorganisms throughout soils, grazing on microbial biomass and mixing of organic inputs within soils and subsequently altering microbial resource accessibility. These invertebrate-mediated pathways may be particularly important because of their influence on soil microbiomes of urban systems. We also propose future research directions aimed at quantifying the influence of invertebrates on soil microbial processes to gain a more comprehensive understanding of urban microbiome function. Understanding the impact of invertebrates on the microbiome of urban systems can potentially lead to better management of microbiomes and enhance microbe-driven ecosystem services.